Respostas
respondido por:
2
P(-1) = x³ - 5x² + x - 2
P(-1) = (-1)³ - 5(-1)² + (-1) - 2
P(-1) = -1 -5(1) + (-3)
P(-1) = -1 - 5 - 3
P(-1) = -9
P(1) = x³ - 5x² + x - 2
P(1) = (1)³ - 5(1)² + (1) - 2
P(1) = 1 - 5 - 1
P(1) = 1 - 6
P(1) = -5
BONS ESTUDOS!
P(-1) = (-1)³ - 5(-1)² + (-1) - 2
P(-1) = -1 -5(1) + (-3)
P(-1) = -1 - 5 - 3
P(-1) = -9
P(1) = x³ - 5x² + x - 2
P(1) = (1)³ - 5(1)² + (1) - 2
P(1) = 1 - 5 - 1
P(1) = 1 - 6
P(1) = -5
BONS ESTUDOS!
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás